Membrane distillation for seawater desalination applications in Vietnam: potential and challenges - Hung, Duong Cong; Nhan, Phan Duc; Tinh, Nguyen Van; Thao, Pham Manh; Nguyen, Nguyen Cong (Vietnam Journal of Science and Technology, 2017)
Desalination of seawater using membrane distillation (MD) can be a practical approach to mitigating the fresh water scarcity in Vietnam. This paper provides a comprehensive review of the seawater MD desalination process. The fundamentals of the MD process including configurations, membrane modules, membrane properties, and heat and mass transfer mechanisms together with approaches to enhancing heat and mass transfer are first systematically reviewed and analyzed. Then, the potential and challenges of the seawater MD desalination process are thoroughly discussed.